Compassion satisfaction, compassion fatigue, burnout, and self-care among South African clinical and counselling psychologists : a cross-sectional mixed methods study - Coetzee, Nicoleen (University of Pretoria, 2021)
Dissertation (MA (Psychology))--University of Pretoria, 2020.